Racism and the crisis of modern conscience. Epistemological and historiographical issues - Burgio, Alberto (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
In these pages, we face the problem of the structure of the reference field of the concept of ‘racism’. We aim to show how, contrary to what is usually claimed, it is possible (and appropriate) to bring the entire racist macro-text back to a unitary logical model (§ 2) and to a common background of meaning, connected to its modern genesis (§ 3); in this regard we suggest seeing in the racist ‘discursive formation’ (in Foucault’s meaning) the antithesis to the fundamental modern ethical principles (§ 4). On this basis, we will formulate a hypothesis regarding the reasons for its rootedness in shared meaning and its growing pervasiveness (§ 5-6), and finally we will highlight the negative consequences of the segmentation of the relative field of research (§ 7).
Keywords: modernity; universalism; discrimination; ethical conflicts; racism